Myocardial fibrosis and inflammation are predictors of heart failure outcomes in people living with HIV. (25th November 2020) - Arendt, C; De Leuw, P; Haberl, A; Stephan, C; Vasquez, M; Arcari, L; Zhou, H; Zainal, H; Albrecht, M; Vogl, T; Zeiher, A; Nagel, E; et al.
Abstract: Background: People living with HIV (PLWH) have higher prevalence of heart failure (HF), which cannot be fully related to traditional cardiovascular disease (CVD) risk factor< or coronary artery disease. Tissue characterisation by cardiac magnetic resonance (CMR), such as with T1 and T2 mapping, is a unique diagnostic approach to provide non-invasive insights into the underlying myocardial pathophysiology. Purpose: To examine prognostic associations of CMR measures, conventional and modified CVD risk scores with HF outcome in PLWH on long-term highly active antiretroviral therapy (HAART). Methods: Consecutive PLWH underwent prospectively standardized evaluation of HF using CMR, risk scores and blood markers. CMR protocol included T1 and T2 mapping, perfusion and scar imaging. MAGGIC, Framingham and D:A:D risk scores were collected. Primary HF endpoint was defined as hospitalization or mortality due to HF, and time-to-even analysis from the index CMR to the first event per patient was performed. Results: 141 PLWH (61% males, 48.0 [40.1–54.6] years, CD4 count 655 [411–909] cells/μl) were included. 16 HF events were observed (12 hospitalizations and 4 deaths) during a median follow-up of 13 [9–16] months. Baseline myocardial native T1, T2, left ventricular volumes and troponin were significant univariate predictors of the HF endpoint. The only signifcant (p<0.001) independent predictor in the multivariate analysis was myocardial native T1 (T1 ≥4 SD, HR (95% CI): 5.0 [1.8–13.4]). Conventional and modified CVD risk scores showed no prognostic association with HF outcomes. Conclusions: Our results show that presence and severity of myocardial inflammation and predominantly diffuse fibrosis detected by T2 and T1 mapping strongly relates to HF events in contrast to conventional and traditional CVD risk scores. Funding Acknowledgement: Type of funding source: Public grant(s) – National budget only. Main funding source(s): The German Centre for Cardiovascular Research (DZHK)